Načelo kontradiktornosti v postopkih prisilne poravnave v praksi slovenskih sodišč - Pengov, Jaka (Pravnik, 2025)
The fundamental purpose of compulsory settlement proceedings is to enable the fastest possible financial, obligation, corporate, and business restructuring of an insolvent debtor, thereby ensuring continued operation of the viable part of its undertaking and offering creditors better prospects of settling their claims than would be available were bankruptcy proceedings instituted against the debtor. To ensure that compulsory-settlement proceedings fulfil this purpose, the court must manage them swiftly and effectively while simultaneously safeguarding creditors’ interests, particularly when those interests are threatened by an abuse of rights within the proceedings. In such cases the court must balance the two most important compulsory-settlement proceedings principles - the expedience (effectiveness) principle and the audi alteram partem (right-to-be-heard) principle - while applying mutatis mutandis, all institutes of "general" civil-procedural law also to compulsory-settlement proceedings. Where appropriate, and having regard to the nature and purpose of compulsory-settlement proceedings, the court may restrict the audi alteram partem principle accordingly. The article sets out the grounds and methods for achieving the foregoing and concludes that no legislative amendments but only the diligent exercise of the existing competences of the court are required for providing for such procedural conduct by the court.
Keywords: "right-to-be-heard" principle; abuse of rights; compulsory-settlement proceedings; expedience principle; hitrost postopka prisilne poravnave; mutatis mutandis application of general rules of civil procedural law; načelo kontradiktornosti; načelo učinkovitosti; postopek prisilne poravnave; prestrukturiranje; restructuring; smiselna uporaba pravil pravdnega postopka; speed of compulsorysettlement proceedings; speed of compulsorysettlement proceedings, mutatis mutandis application of general rules of civil procedural law; zloraba pravice